Patterns of emergency department use in rural and metropolitan New South Wales from 2012 to 2018. (27th September 2020) - Lower, Tony; Kinsman, Leigh; Dinh, Michael M.; Lyle, David; Cheney, Richard; Allan, Julaine; Munro, Alice; Taylor, Barbara; Wiggers, John H.; Bailey, Andrew; Weller, Lauren; Jacob, Alycia; et al.
Abstract: Objective: To explore the patterns of and investigate the factors associated with rises in emergency department presentations in rural and metropolitan New South Wales from 2012 to 2018. Design: A retrospective descriptive study of de‐identified data from the New South Wales Emergency Department Data Collection. Setting: New South Wales, Australia. Participants: All individuals presenting to 99 New South Wales emergency departments, which continuously reported to the Emergency Department Data Collection between 2012 and 2018. A total of 2 166 449 presentations recorded throughout New South Wales in 2012 (rural 786 278; metropolitan 1 380 171) and 2 477 192 in 2018 (rural 861 761; metropolitan 1 615 431). Main outcome measures: Total emergency department presentations, plus Poisson regression modelled annual changes in emergency department presentations over the period 2012‐2018. Results: Growth in emergency department presentations outpaced population growth in both rural and metropolitan New South Wales between 2012 and 2018. The patterns of age‐standardised rates of presentations were broadly similar between rural and metropolitan areas, with highest rates observed in the youngest (0‐4 years) and oldest (85+ years) cohorts. The rural sample also displayed a distinct third peak in ages 15‐39 years, and rates were higher across all age groups. Rural New South Wales displayed disproportionately higher emergency department presentations in the two most deprived socio‐economic status quintiles. While rural New South Wales displayed significant reductions in triage category 5 (non‐urgent cases) over time, the relative proportion remained approximately double that of metropolitan sites. Conclusions: There are differences between rural and metropolitan emergency department presentations relating to demographic factors, triage levels, acuity and admissions. Detailed local investigations are required to determine specific contextual issues that impact on emergency department demand.